Nitrous Oxide Formation by Corona Discharge: Isotopic Composition Measurements and Atmospheric Applications. Issue 8 (26th April 2021) - Smith, Mica C.; Carlstad, Julia M.; Hunter, P. Quinby; Randazzo, John; Boering, Kristie A.
Abstract: The expanding use of nitrogen‐containing fertilizers in agriculture has led to an increase in N2 O, an important greenhouse gas and ozone‐depleting substance, since preindustrial times. Isotopic measurements are a valuable tool to distinguish the contribution of different sources of N2 O, but the isotopic composition of N2 O formed in the low temperature plasma regimes in lightning has not previously been measured. Here, a corona discharge was generated in flowing or static zero air, and the N2 O formed at discharge cell pressures from ∼0.1 to 10 Torr (∼13–1, 300 Pa) at a discharge voltage of 5 kV and discharge current of 1, 500 μA was collected and measured by isotope ratio mass spectrometry. Experiments were also conducted by varying the discharge current from 75 to 1, 500 μA at ∼0.5 Torr (∼67 Pa) and 5 kV. The results show enrichments in 15 N in product N2 O of up to 32‰ relative to the reactant N2 and even larger enrichments in 15 N of up to 77‰ at the central nitrogen atom. Depletions in 18 O as large as −71‰ relative to reactant O2 were also measured. The isotope‐isotope relationships of the N2 O produced in the corona discharge are distinct from those of other sources of N2 O, suggesting that isotope measurements can be used to determine whether local or regional variations in the atmospheric concentration of N2 O – such as the enhanced N2 O levels measured in the upper tropical and subtropical troposphere during the HIPPO mission – can be attributed to lightning activity, soil emissions, or biomass burning. Key Points: N2 O produced in a 5 kV corona discharge in 10 Torr N2 /O2 is enriched in 15 N and depleted in 18 O relative to the initial air mixture Isotopic composition measurements can help constrain mechanisms of N2 O formation and destruction in a corona discharge The influence of local lightning activity on N2 O in the upper tropical troposphere may be identifiable by its distinct isotopic signature